A comprehensive review on water management strategies and developments in anion exchange membrane fuel cells. (31st July 2020) - Gutru, Rambabu; Turtayeva, Zarina; Xu, Feina; Maranzana, Gaël; Vigolo, Brigitte; Desforges, Alexandre
Abstract: In spite of significant achievements in alkaline exchange membrane fuel cells (AEMFCs) in recent years, they are still lagging behind proton exchange membrane fuel cells (PEMFCs) due to performance instability. Among the relevant operational parameters of AEMFC, the researchers have found that poor water management within the cell was the main reason for failure of the system. In the past five years, numerous modeling and experimental works were reported proposing different strategies to improve water management of AEMFC. With proper water management, the achievable power output in AEMFCs is comparable with that of PEMFCs or even more. Efforts have to be continued, but AEMFCs can become a strong competitor in the market place. This review paper discusses the strategies and developments impacting water management of AEMFCs providing knowledge source for upcoming studies. Highlights: Water dynamics are more complex in AEMFC than PEMFC. PTFE in GDL plays crucial role in water management. Pt and ionomer loading in the electrode strongly impacts water management. AEM with low diffusion resistance mitigates anode flooding. Operating conditions ( RH, T ) should be optimized for stable AEMFC performance.